Comparison of Oncological Outcomes After Curative Resection for Right-side Colon Cancer and Left-side Colon Cancer: a Retrospective Observational Study - Mehmet Torun; Orhan Uzun; Mustafa Duman; Erdal Polat; Aziz Serkan Senger; Mürşit Dinçer; Ömer Özduman; Selçuk Gülmez; Ahmet Orhan Sunar (Turkish Journal of Colorectal Disease)
Aim: This study aims to compare clinicopathological findings and oncological outcomes after curative resection between right-side colorectal carcinoma (RCC) and left-side colorectal carcinoma (LCC). Method: A retrospective review of 209 patients who underwent elective surgery for right and left colon cancer between January 2013 and October 2022 was conducted. After applying the exclusion criteria, 182 patients were included. The patients were grouped based on embryological development: right side (cecum, ascending colon, hepatic flexure, and proximal transverse colon) and left side (distal transverse colon, splenic flexure, descending colon, and sigmoid colon). Clinicopathological features, lymph node removal, and oncological outcomes were compared. Statistical analyses were performed using the chi-squared test, Fisher’s exact test, Mann-Whitney U test, the Kaplan-Meier method, and Cox regression analysis. Results: Among the 182 patients, 108 (59.3%) had RCC, and 74 (40.7%) had LCC. No significant differences were found between the groups regarding age, gender, body mass index, carcinoembryonic antigen value, tumor size, T/N stage, lymphovascular/perineural invasion, positive lymph nodes, and hospital stay. However, more lymph nodes were removed in RCC cases (p<0.0001). Oncologically, 32.4% of the patients with RCC and 29.7% of the patients with LCC died during follow-up, with no difference in mean survival. Multivariate analysis identified age and tumor size as prognostic factors for 5-year survival. Conclusion: Despite clinical and pathological differences between RCC and LCC, no significant difference was observed in 2- and 5-year survival. Early diagnosis and personalized treatment remain crucial for both cancer types. Further large-scale studies are recommended.